Peran Orang Tua dalam Melestarikan Nilai-Nilai Tradisi Ngitung Batih pada Anak Usia 4-6 Tahun di Desa Dongko Kabupaten Trenggalek - Agustina, Suryani Eka; Roesminingsih, Maria Veronica (J+PLUS UNESA, 2023)
This study aims to determine the meaning of ngitung batih traditional values and the activities of parents in dongko village to preserve ngitung batih traditional values to children aged 4-6 years. The research method used is qualitative descriptive. The results showed that the role of parents in preserving the values of ngitung batih tradition in children aged 4-6 years is that in ngitung batih tradition, children can learn how to communicate with parents. They will understand etiquette and manners and how to apply them appropriately and according to the situation. By introducing ngitung batih culture, it is very relevant and effective to shape children's ethics and manners. Not only the value of courtesy but also the values that can be obtained such as the value of harmony, religion, and mutual assistance. It can be concluded that the values contained in the ngitung batih tradition are very diverse and have their own benefits for children and parents play an important role in preserving the values of the ngitung batih tradition, especially for their children from an early age.